Demographics and Clinical Profiles of Patients Visiting a Free Clinic in Miami, Florida - Zhang, Michael; Garcia, Alejandro; Bretones, Gisela (Frontiers in Public Health, 2019)
Background Although the ranks of the uninsured in the United States have decreased in recent years, some states still lack Medicaid expansion programs, leaving many Americans, especially the indigent and homeless, without adequate healthcare coverage. Free-for-care clinics are oftentimes the last safety net for these vulnerable populations. Because these clinics have limited funding, a thorough understanding of the patients they serve is necessary to effectively direct their resources. The objective of the present study is to investigate the characteristics and clinical profiles of patients utilizing a free clinic in Miami, Florida. Methods Aggregate EMR data reflecting consecutive adult patient visits to the Miami Rescue Mission Clinic in Miami, Florida between January 1st, 2018 to March 15th, 2019 (n=846) were reviewed for sociodemographic data and chronic disease prevalence. Prevalence rates were compared by gender and to county estimates from the Florida Behavioral Risk Factor Surveillance System. Results The most common conditions were mental health (19.3%), circulatory system (14.7%), and musculoskeletal system disorders (13.9%). Males had a greater prevalence of depression (difference = 6.6%; 95% CI [1.5 to 10.7%]; χ2 = 6.2; p = 0.013) and overall mental illness (22.0 vs 10.4%, difference = 11.6%; 95% CI [5.7 to 16.4%]; χ2 = 13.2; p = 0.0003) compared to females. Also, males had a higher prevalence of depression (difference = 6.4%; 95% CI [2.1 to 10.2%]; χ2 = 8.0; p = 0.0047) and HIV (difference = 1.4%; 95% CI [0.3 to 3.0%]; χ2 = 7.3; p = 0.007) compared to county estimates. Rates of hypertension, diabetes, elevated cholesterol, asthma, and COPD were lower in the clinic population compared to the surrounding county. Conclusion There is an acute need for mental health services in this population. The lowered prevalence of other chronic conditions is due to underdiagnosis and loss to follow-up.